Download presentation
Presentation is loading. Please wait.
Published byCharla Hudson Modified over 6 years ago
1
What is an equation? An equation is the equality of two different expressions. This equality is true only for a number of dinstinct values (or none) of the unknow quality. This process of finding these values is called….
2
Solving equations -2x + 1 = 2 (4+8) + 1 -4x
One or both of the expressions may contain variables, in a linear equation they are usually indicated with an ‘x’. Solving an equation means manipulating the expressions and finding the value of the variables. An example might be: -2x + 1 = 2 (4+8) x
3
Solving equations -2x + 1 = 2 (4+8) + 1 -4x -2x +4x= 2 (4+8) + 1 - 1
to solve this we have to put all the known terms on the same side and simplify them. When we move a term from one side to an other, we have to change its sign. -2x +4x= 2 (4+8) Now we find out the value of the second side and then we divide every side by 2. 2x/2 = 24/2 x= 12
4
Properties To keep an equation equal, we must do exactly the same thing to each side of the equation. If we add (or subtract) a quantity from one side, we must add (or subtract) that same quantity from the other side. To solve this equation we would add 3 to both sides. The equation would become x = This becomes x = or x = 8.
5
Quadratic equations When a quadratic expression has a particular value, we have a quadratic expression. x2+5x+6=0 It can be written in the general form: ax²+bx+c=0 The terms are not always given in this order and they should be arranged into the standard form. A quadratic expression can be solved in more than one different way.
6
Solution by factorising
Consider the equation x2+5x+6=0. This can be factorized into (x+2)(x+3)=0. So the solutions must be x1=-2 and x2=-3 because when we substitute any of the two values in the given equation, we obtain zero.
7
The formula for solving a quadratic equation
Using the general quadratic equation, we can reach a formula that can solve every equation in variables x,x2.: ax²+bx+c=0 First we isolate the known term; ax²+bx=-c 2) Then we divide all the terms by a on both sides: x²+[(b/a)(x)]= -c/a
8
The formula for solving a quadratic equation
3) We write the term b/a as a double product: b/a (x) =2(x) b/a X²+2(x) (b/2a)= -(c/a) 4) We add to both sides the term (b/2a) ² ; making this we complete the square: X²+ b/a(x) + (b/2a)²= -(c/a) + (b/2a)²
9
The formula for solving a quadratic equation
5) The trinomiol of the first side it’s the square of the binomiol we were looking for: (x+ b/2a) ²= - (c/a) + (b²/4a²) = ( b²- 4ac/4a²) V(b2 - 4ac) 6) (x+b)/2a = a2
10
The formula for solving a quadratic equation
-b + V(b2 - 4ac) 6)x1 = 2a -b – V(b2 – 4ac) x2= 2a
11
The formula for solving a quadratic equation
7) These values we found out are the solutions of our equation: ax²+bx+c=0.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.